Haar transformation of linear boolean function - Mohamed Rafiq, Hashum; Siddiqi, Muhammad Umar (2009)
Haar transform is known to have the smallest computational requirement with a considerable interest and attraction drawn towards its spectral properties of Boolean functions. This paper presents Haar transform of Linear Boolean functions, where by the discussion is based on the transformation from the Boolean domain to the Haar domain. The resulting spectrum is given with the corresponding calculations presented, while the analysis of the respective spectral coefficients and their general properties being explored. Furthermore, the general formulation and/or equation derivation for the transformation is introduced.